2019
DOI: 10.5604/01.3001.0013.4607
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistance of hydrogenated high nitrogen steel at dry and solid state lubricants assistant friction

Abstract: Purpose: This paper is devoted the investigation hydrogen influence on of wear resistance of high nitrogen steel (HNS) at dry and solid state lubricants assistant friction. It has been established that after hydrogenation at 250 N loading the wear rate increased by 2.9 ... 4.1 times. Microhardness of hydrogenated layer was 7.6 ... 8.2 GPa, that is increased after hydrogenation in two times. After adding the (GaSe)xIn1-x compounds to the tribo conjugates by X-ray diffraction analysis it has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In addition, the graphite veins in the ring structure serve as oil reservoirs and counteract the destruction of the oil film under adverse operating conditions. We also found that high-nitrogen steels can hold well on their surface layered coatings, not only of graphite origin, and reduce the intensity of wear [26,27].…”
Section: State Of the Artmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, the graphite veins in the ring structure serve as oil reservoirs and counteract the destruction of the oil film under adverse operating conditions. We also found that high-nitrogen steels can hold well on their surface layered coatings, not only of graphite origin, and reduce the intensity of wear [26,27].…”
Section: State Of the Artmentioning
confidence: 88%
“…We have established that high-nitrogen steels can hold a layer of adsorbed layered lubricants on their surfaces for several hours (in the absence of lubrication) [25,26]. This feature is associated with the characteristics of the surface layer formed in a number of technological operations.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…This process contributes to intensive wear [2][3][4][5][6][7][8][9][10]. Authors [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have analyzed the features of hydrogen wear of construction machine parts.…”
Section: Introduction State Of the Art And Problem Formulationmentioning
confidence: 99%
“…The ways of surface hydrogenation are established, the mechanism of hydrogen wear of machine parts and equipment is discussed, and the methods of protection against tribohydrogen saturation are formulated [10]. On the other hand, the interaction of hydrogen with metals and non-metallic elements [19][20][21][22][23] and its influence on various properties of metals, alloys, hydrogen-induced specific defects, and hydrogen embrittlement, as well as the effect of hydrogen on the mechanical characteristics in the "hydrogen-metal" couple, are assessed [1,2,10].…”
Section: Introduction State Of the Art And Problem Formulationmentioning
confidence: 99%